A new record of Psilocybe (Fungi, Basidiomycotina, Agaricales) in Argentina - Moyano, Alejandro José; Daniele, Graciela María (Instituto de Ecología, A.C., 2003)
An extension of the known distribution and substrate is reported for Psilocybe pegleriana. This constitutes the most austral record of the species for America and it is the first record for Argentina.